Suitability of Bhagavad-Gita as a bibliotherapuetic tool in a post war society of Sri Lanka – a Librarian’s view - Navaneethakrishnan, S.; Sivasamy, V. (13th Annual Research Symposium of the Faculty of Graduates Studies (FGS), University of Kelaniya, 2012)
Life is a continual adjustment to many different types of problems and many people face problems stemming from handicapping conditions, language differences, and the post war situation in Sri Lanka. Poverty, destructive pastimes and inability to cope up with stressful situations, divorce, displacement, failure, illnesses, and disabilities were the main causes for distress and mental stress of the people in various ways. The librarian occupies a strategic position in the development of emotions of the people, and it is felt that this is the opportune time to take serious note of the social needs as well as health care necessities of these post war society in Sri Lanka. This study was carried out to help and shape the future of those who are experiencing stress and crises in their lives due to the post war situation. Bibliotherapy as a term is derived from two Greek words biblio meaning "book" and therapia meaning "healing" and refers simply to "The use of reading materials to help in solving personal problems or for any psychiatric therapy”. Kirklees - the library in USA has recently (2012 January) started to use text messaging to enhance and improve its bibliotheraphy service. Objective of the study is to find out the significant features of Bhagavad –Gita as an appropriate bibliotherapuetic tool literature in a post war society. Qualitative aspects of Bhagavad-Gita are analyzed in this study based on the descriptive methodology, which involves study, understanding and interpretation of the above ancient and classical text. A review of literature in this field shows that several studies have been done in the area of bibliotheraphy from various perspectives; however very few have been done to integrate the specific literatures except Bhagavad-Gita. As a result, this paper not only fills the gap in the literature of bibliothetraphy, but also provides some new significant features of Bhagavad- Gita as a bibliotherapuetic tool from the library science perspective. Through this study it is identified that some significant instructions of Bhagavad- Gita help readers to develop positive self-image, relieve emotional pressures, develop new interests, create a desire to emulate models, promote tolerance, encourage realization that there is good in all people and stimulate decision making through critical thinking. When the post war society in Sri Lanka read the Bhagavad-Gita their minds become more articulate and their nervous system is stimulated. Now they feel a new strength with courage. They become tolerant, patient and forgiving. Egoism falls away from them. It sends them back to active life with renewed hope, zest and vigour. In a nutshell, as the Bhagavad-Gita helps its readers by creating affective and cognitive changes, it is an appropriate bibliotherapuetic tool literature in a post war society of Sri Lanka.
Keywords: Library Services; Bibliotheraphy; Bhagavad – Gita; Psychology